A Case Study of Bank Accounting Practices on Reserves for Impairment of Credit Deduction - Nanang Shonhadji (Universitas Hayam Wuruk Perbanas, 2017)
The objectivity of the customers' feasibility is biased with the interest of the targeted credit that they are assigned to achieve. In addition, it remains an obstacle forsmall and medium class banks to be dependant on the long historical credit data of each customer to determine the credit-value loss (CKPN). Â This study uses a method of a qualitative case study with structured stages for determining the formation of credit-value loss (CKPN) with creditrisk+ model. The purpose of this study is to reveal the accounting practice of establishing CKPN with creditrisk+ model. The results show that the ATMR method caused BPR banks to provide a very large recovery fund when compared with CreditRisk+ method. Other findings reveal that the approach of ATMR is not maximized in producing accurate measure of credit risk and in accordance with the actual condition. This study contributes to providing an alternative to the determination of CKPN in addition to using ATMR and roll rate analysis model by the banks. For the regulators and professional organizations of the Indonesian Institute of Accountants, they can use it as sources of information to evaluate the application of PSAK 55, especially in determining the CKPN.Â